Contribution to hair and skin science in Indonesia through a research grant program - Verschoore, Michele; setiawan, rhadeya; Listiawan, Muhammad Yulianto; Nurtami, Nurtami; Moreau de Montcheuil, Eloïse (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
To foster scientific advances in basic and clinical research projects, a philanthropic "hair & skin research grant" program was launched in 2021 through a partnership between University of Indonesia, Perdoski, and L’Oreal Research and Innovation. The aim of the program is to empower Indonesian scientists to generate research data on general skin and hair issues that affect the Indonesian population. We have grouped the eight grant projects awarded between 2021 and 2022 into five main themes: skin type characterization; skin microbiota; botanical extracts; photoaging therapies; and hair loss. The various studies are evaluating potential therapies for acne, skin aging, photoaging and male androgenetic hair loss (alopecia). The data will be useful for the development of guidelines for hair and skin care practices to raise awareness and educate the general public of Indonesia on the importance of skin and hair health.